2019
DOI: 10.3329/bjnm.v22i1.40506
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D Status in Newly Diagnosed Hypothyroid Patients

Abstract: More than billion people worldwide are vitamin D deficient. It is recognized to have function in bone and muscle development by regulating calcium and phosphorus metabolism. Its role as an immune modulator has recently been discovered. Deficiency of vitamin D has been discovered to be associated with various cardiovascular, infectious, malignant, hypothyroidism and autoimmune thyroid diseases. Prevalence of hypothyroidism and hypovitaminosis D in Bangladesh is not known but supposed to be high because our neig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
2
4
1
Order By: Relevance
“…Conflicting results are found in this era, where some articles found the same results [13], others showed the opposite [20]. These differences may be explained by several Although this is a less statistically significant positive relation, our data does not match with other studies that showed decreased vitamin D with age [21,22].…”
Section: Methodscontrasting
confidence: 85%
See 2 more Smart Citations
“…Conflicting results are found in this era, where some articles found the same results [13], others showed the opposite [20]. These differences may be explained by several Although this is a less statistically significant positive relation, our data does not match with other studies that showed decreased vitamin D with age [21,22].…”
Section: Methodscontrasting
confidence: 85%
“…Many studies were conducted to find if there is an association between vitamin D deficiency and hypothyroid disorders, whether vitamin D involved in pathogenesis or even a sequalae of a thyroid illness [13,18,19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Khan et al 39 measured vitamin D3, TSH, and FT4 in the hypothyroid group (24 females, 14 males 37.82 ± 7.95 years) and euthyroid group (34.84 ± 8.61 years). The mean level of vitamin D for the euthyroid group was17.11 ± 5.62 ng/mL, and for the hypothyroid group itwas13.16 ± 4.29 ng/mL.…”
Section: Studies About the Relation Of Hypothyroidism With Vitamin Dmentioning
confidence: 99%
“…A serum level of thyroid stimulating hormone (TSH) above the established upper limit of the reference range and a serum level of free thyroxine (fT4) within the reference range is termed subclinical hypothyroidism (SCH) (4). Globally, subclinical hypothyroid dysfunction is more common than overt disease (10). Limited studies discussed the vitD levels in SCH (11).…”
Section: Introductionmentioning
confidence: 99%